IN SILICO MOLECULAR MODELING AND DOCKING STUDIES OF NANO COMPOSITES COMPOUND TO REGULATION, INHIBITION AND TREATMENT LEAF AND STEM WHEAT RUST - Israa Mohamed Shamkh; Dina Pratiwi; Mohammed F. Abo El Magd; Ahmed Salih El Faki (Jurnal Farmagazine, 2021)
Puccinia graminis f. sp. tritici (Pgt) and P. triticina (Pt), the causal agents of stem and leaf rust, respectively form new physiological races that significantly reduce growth and yield of wheat cultivars. Therefore, seeking for exploring if there an inhibition effect of the Nano Composites compound on leaf and stem rust to regulation, inhibition and treatment leaf and stem wheat rust objectives to continuously produce new wheat pesticides resistant to stem and leaf rust. The aim of the study was to finding natural and Nano compounds to control, treatment and regulation of wheat rust. In this study we used molecular modeling and docking for the two vital proteins in stem and leaf wheat rust MAP kinase 1 [Puccinia triticina] and PGTG Puccinia graminis f. sp. Tritici. In the silico analysis, the two vital proteins activity is suppressed and inhibited In this work the chitosan and chitosan –Cu which selected for the study are considered as safe compounds the compounds showed interaction with the MAPK1 and PGAT proteins Thus the bioactive compounds that are interacting with the target can be used as a potent inhibitor to block the action of our proteins.